pH-Responsive One-Dimensional Periodic Relief Grating of Polymer Brush-Gold Nanoassemblies on Silicon Surface - Chen, Jem-Kun; Pai, Ping-Chun; Chang, Jia-Yaw; Fan, Shih-Kang (My University, 2012)
In this work, we focus on the fabrication of the nanoassemblies consisting of the poly(2-dimethylaminoethyl methacrylate) (PDMAEMA) brushes and gold nanoparticles (AuNPs). The employed process involves grafting of the PDMAEMA chains on an underlying substrate in a brush conformation followed by the immobilization of surface functionalized AuNPs by means of physical interaction (electrostatic attraction, entanglement, and hydrogen bonding). Atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and UV-vis spectroscopy have been employed to characterize the prepared PDMAEMA-AuNP nanoassemblies. Polymer brushes possessing various thicknesses have been found to suppress the nanoparticles' aggregation and, hence, facilitate the surface coverage. Furthermore, we patterned the PDMAEMA-AuNP nanoassemblies as an one-dimensional periodic relief grating (OPRG). The subwavelength structure of OPRG has the optical features including artificial refractive index, form birefringence and resonance and band gap effects. A mean refractive index of the PDMAEMA-AuNP nanoassemblies can be controlled by the filling factors of the OPRG structure, so that a desired distribution of refractive index of the polymer brushes-gold OPRG under various stimuli can be realized. The employed approach is simple and highly versatile for the modification of surfaces with a wide range of NPs.
Keywords: PDMAEMA brush; nanolithography; gold nanoparticles; binary grating